Targeting the brain-gut-prostate axis in chronic prostatitis: mechanisms and therapeutics - Song, Shiwei; Zhang, Chunlei; Zhang, Bin; Yin, Jinlong; Yu, Chang; Wang, Xuanrong; Wang, Qing; Ma, Fulin; Yang, Changfeng; Chang, Dehui (Frontiers in Endocrinology, 2025)
Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), a refractory urinary system disorder, is closely associated with dysregulation of the brain-gut-prostate axis. Emerging evidence highlights the pivotal role of gut microbiota dysbiosis and its bidirectional interactions with the neuroimmune system in CP/CPPS pathogenesis. This systematic review integrates perspectives from microbiomics, neuroimmunology, and metabolomics to propose a theoretical framework of the brain-gut-prostate axis and multi-dimensional therapeutic strategies targeting this axis. By transcending conventional localized anti-inflammatory approaches, these strategies aim to address clinical resistance and phenotypic heterogeneity. Mechanistic insights into microbiota-derived metabolites (e.g., short-chain fatty acids, SCFAs), neuroendocrine signaling (e.g., thyrotropin-releasing hormone, TRH), and immune crosstalk (e.g., Th17/Treg imbalance) are explored, alongside innovative therapies such as microbiome modulation, neural interventions, and immune regulation. This holistic paradigm not only provides new mechanistic insights but also offers promising avenues for personalized management and translational research in CP/CPPS, potentially overcoming current therapeutic bottlenecks.